Can foreigners offer civil resistance to the authorities of the host country? A critical reevaluation of “civil resistance” in the fields of civil resistance studies and Hannah Arendt studies - Bragdon, Thomas (HannahArendt.net, 2024)
In the years prior to movements such as #RhodesMustFall, Black Lives Matter and Extinction Rebellion, protest movements organized by asylum seekers emerged, such as the Berlin Refugee Movement, Sans Papiers and We Are Here. The limelight has shifted away from them, but they continue to subsist. This type of movement stands for a form of resistance whose full implications are yet to be assessed. Refugee Movement – or any similar movement – has yet to be studied in the field of civil resistance studies. In this paper it is argued that the epistemic disregard for such movements is due to a restrictive understanding of the adjective civil in “civil resistance.” Leading civil resistance scholar Erica Chenoweth equates “civil” with “civic,” which is derivative from the noun citizenship. This restrictive equation implies that civil resistance as a term only pertains to citizen movements. Yet, it is argued in this paper, some movements led by noncitizens may be taken to partake in civil resistance too. Refugee Movement, for instance, organizes protests that manifest typical characteristics of civil resistance. Since they should matter for civil resistance studies, it is argued that “civil” relates to a third term that is distinct from the citizen and the foreigner. It refers rather, it is argued, to the technical term of the civilian: the resident with or without the citizenship status who is subject to the civil law of the host country. The above-described semantic revision of civil resistance has relevance for not only civil resistance studies but also Hannah Arendt studies. This revision implies a renewed consideration of the assumptions of the efficacy of civil resistance. Gene Sharp, founder of civil resistance studies, brings forth an early theory of the efficacy of civil resistance in the seventies of the last century. He acknowledges that his theory is indebted to Arendt’s notion of power in On Revolution. Arendt’s text should be revisited, it is argued, to revise Sharp’s account of civil resistance. It will be argued that if the field of civil resistance studies relies on Arendt’s notion of power, it should be possible to study the forms of protest of Refugee Movement through the lens of civil resistance. Moreover, Sharp’s evaluation of On Revolution occasions a reevaluation of this contested text in the literature. Three objections against Arendt’s notion of the political will be discussed: first, the objection that for Arendt authority is based on unreflective forces such as habit and belief; second, the objection that Arendt has a purified notion of the political; third, the objection that she offers too restrictive descriptions of the “techniques of struggle” (Sharp) that exemplify her notion of power. Whereas the first two objections may be refuted, the last objection is a substantial one that invites to a revision of her notion of the political within civil resistance studies. This, it is argued, broadens the scope of civil resistance studies to include the study of movements such as Refugee Movement.